Experimental evidence of co-existence of equilibrium and nonequilibrium in two-glass-transition miscible mixtures. Issue 44 (5th November 2020) - Jin, Xiao; Guo, Yuxing; Tu, Wenkang; Feng, Shidong; Liu, Yingdan; Blochowicz, Thomas; Wang, Li-Min
Abstract : Two glass-transitions have been observed in some miscible molecular mixtures with notable differences in geometry or chemistry of constituents. Ageing between the high and low glass transitions confirm the co-existence of nonequilibrium and equilibrium states in the regions. Abstract : Two glass-transitions have been observed in some miscible molecular mixtures with notable differences in geometry or chemistry of constituents. The explanation of the phenomena has been puzzling with diverse structural models. Here, we present detailed studies on two glass-transition mixtures composed of tripropyl phosphate (TPP) and polystyrene (PS) by using calorimetric and dielectric measurements. We found that ageing between the two transitions always generates endothermic peaks at temperatures ∼4 K higher than the ageing temperatures and, subsequent thermal cycles around the peaks can remove the ageing effect and restore the systems, confirming the co-existence of nonequilibrium and equilibrium states in the regions. We also found that the broad glass transition thermogram is associated with highly stretched relaxation dynamics. The results allow us to draw a conclusion of continuous mobility gradient spanning the two TPP–PS glass-transitions, rather than complete phase separation.